Designing effective and acceptable policy mixes for energy transitions: Countering rebound effects in German industry. (August 2022) - Kern, Florian; Peuckert, Jan; Lange, Steffen; Ahmann, Lara; Banning, Maximilian; Lutz, Christian
Abstract: Energy efficiency policies leading to energy demand reductions are a crucial component of ambitious energy transition strategies. However, rebound effects have been suggested to reduce energy demand reductions from energy efficiency improvements. Such effects have been studied extensively in the literature, but there has been less focus on the question whether (and if so, how) policy action can deliberately counter rebound effects. Also most of the existing literature focuses on households, while rebound effects also occur within industry. In order to address this knowledge gap, we build on the growing literature on policy mixes for transitions. Using a mixed methods approach combining macroeconomic modelling with qualitative stakeholder interviews and workshops, the paper investigates for Germany whether complementing an industrial energy efficiency programme with a number of other policy instruments can counter rebound effects. It assesses the economic impacts of the proposed policy mixes as well as their political acceptability. Our analysis finds that complementing a public funding scheme for industrial energy efficiency investments with other policy instruments can counteract rebounds, but faces a number of challenges in terms of acceptability. The paper argues for a more informed and honest policy and societal debate about rebound effects in order to boost problem awareness and agenda setting and to create a positive narrative around tackling rebounds. The main contribution of the paper is to show how important it is to take political factors into account in the design of policy mixes. It also showcases a mixed methods approach combining modelling with qualitative research which we see as very promising for analysing policy mixes.